Pengaruh Reward terhadap Kinerja Karyawan CV Teknika Kreasindo di Kota Makassar - Inda Alfiah N; Siti Hasbiah; Agung Widhi Kurniawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to determine the effect of rewards on the performance of CV Teknika Kreasindo employees in Makassar City. The variables in this research consist of the independent variable, namely Reward, and the dependent variable, namely employee performance. The population and sample in this research are all CV employees. Teknika Kreasindo in Makassar City. The data collection techniques used were observation and questionnaires. The data analysis technique used is simple linear regression analysis with SPSS version 26 software to prove the hypothesis. The results of this research show that there is a positive and significant influence between the rewards given by the company on employee performance. These findings indicate that providing appropriate rewards can increase employee motivation and work productivity, so that they can contribute to organizational achievements. It is hoped that this research can provide a reference for companies in designing effective reward systems to improve employee performance.